Akibat Hukum yang Timbul atas Terjadinya Kejadian Ikutan Pasca-Imunisasi pada Pelaksanaan Program Imunisasi Dasar Lengkap di Provinsi Banten - Asmawati Asmawati; Muhyi Mohas; Rani Sri Agustina (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
This study aims to analyze the legal consequences arising from the occurrence of Post Immunization Adverse Events (KIPI) in the implementation of complete basic immunization in Banten Province. This type of research uses a normative juridical approach. Based on the results of the study, it is known that the legal consequences of the occurrence of AEFI in the implementation of immunization, both those who practice outside their authority and if an error occurs due to negligence can be subject to "disciplinary sanctions, administrative sanctions, civil and criminal". The imposition of sanctions must meet the requirements of professional ethics and discipline (there is a violation of the code of ethics and professional discipline); In terms of administrative law in the form of abuse of authority; In terms of civil law in the form of a lawsuit based on contractual liability, namely non-compliance with professional standards, service standards and SOPs; and In terms of criminal law, there is an element of error in the form of intentional and/or negligence on the part of the health officer providing immunization.